Implementation of the Concept of Islamic Religious Education According to Imam Ghozali in Improving Students' Psychomotor Skills - Ahmad Farzai; Idzi' Layyinnati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Nowadays, students rarely apply the material. This can hinder their psychomotor development. This phenomenon is supported by learning materials that focus on cognitive development in students, which is certainly irrelevant. The purpose of this study is to examine Imam Ghazali's ideas on Islamic religious education, which, if implemented in schools, can improve students' psychomotor abilities. The study will also analyze how these ideas contribute to improving students' psychomotor abilities in today's era. The researcher used a qualitative research method with a field research approach. To ensure data validity, data triangulation techniques were used to analyze the data. The results of the research analysis indicate that the concept of Islamic religious education is still highly relevant for implementation in schools. This concept focuses not only on cognitive development but also on psychomotor development. Every human development must involve three aspects: cognitive, affective, and psychomotor. Otherwise, the development of these three aspects can reduce the quality of a person. According to Imam Ghazali, the student learning process is not only about being given theory or material, but also requires practice to ensure that understanding of the material is conveyed perfectly.